2018
DOI: 10.1111/twec.12673
|View full text |Cite
|
Sign up to set email alerts
|

The global financial crisis and the mutual fund flow–performance relationship

Abstract: Existing research shows mutual fund flow is highly correlated with past performance in an asymmetric way, namely flow–performance convexity. Fund managers pursue incentives to manipulate fund characteristics to invoke future fund inflows. Given this body of evidence, how has the global financial crisis impacted on fund volatility and fee structures with respect to the flow–performance relationship? Using data for the period 1999 to 2011 (disaggregated into three sample periods) for US mutual equity funds, empi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 86 publications
(159 reference statements)
3
26
0
Order By: Relevance
“…Inverse conclusions about well-and moderately-performing funds have been reported by Ferreira et al [22]. Wang et al [23] found that a back-end load will shrink net flow-performance sensitivity. Differing from those studies, Navone [24] firstly stated that investors consider operating expenses and performance to be equally important and explored the effect of performance on the relationship between fund flow and operating expenses.…”
Section: Effect Of Performance On the Flow-fee Relationshipmentioning
confidence: 89%
See 2 more Smart Citations
“…Inverse conclusions about well-and moderately-performing funds have been reported by Ferreira et al [22]. Wang et al [23] found that a back-end load will shrink net flow-performance sensitivity. Differing from those studies, Navone [24] firstly stated that investors consider operating expenses and performance to be equally important and explored the effect of performance on the relationship between fund flow and operating expenses.…”
Section: Effect Of Performance On the Flow-fee Relationshipmentioning
confidence: 89%
“…For the load fee, in the U.S. market, funds are purchased directly with fund underwriters or indirectly via brokers; the load fee is the fee charged by brokers or advisors for their services [12]. Mixed results suggest that the load fee has a two-sided effect on fund flows: a high load fee reduces the search cost due to its advertising role and increases the net flow [15,36]; a high load fee is regarded as a burden on the return of funds due to its salience and decrease in the net flow [23,37,38]. Barber et al [13] demonstrated that the negative effect of load fee salience always offsets the advertising role of the fee.…”
Section: Effect Of Fund Fees On Mutual Fund Flowsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent trend in the literature focuses on the importance of volatility as a measure of risk due to its role in affecting investors' behavior and the market direction. Busse (1999) suggests that mutual fund performance is associated with market volatility, and a recent paper by Wang et al (2018) provides evidence of investors' reaction to the volatility level of the market. Jordan and Riley (2015) investigate the relationship between funds' performance with market volatility.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The mutual fund industry has attracted the interest of academics and financial market participants due to the rapid growth of total assets under management over recent decades. The finance literature has provided a large body of work on mutual fund performance from different aspects (e.g., Cuthbertson et al, 2016;Wang et al, 2018;Wulfmeyer, 2016). The existing literature provides a sufficient analysis of developed markets, whereas emerging markets have received relatively little attention despite their accelerated growth, dynamic change and rapid influence on the world economy.…”
Section: Introductionmentioning
confidence: 99%